The Influence of Green Product Strategy, Green Promotion, and Brand Image on Environmental Awareness and Its Impact on Purchase Decision for Panasonic Inverter AC Products - Sandra Arviya; Ramli, Yanto (ARE Publisher, 2024)
This research aims to analyze the influence of green product, green promotion, and brand image strategies on environmental awareness and the impact on purchase decisions. The population of this research is inverter AC users who live in Tebet District, with a total sample of 200 respondents. The data analysis method uses the Structure Equation Modeling (SEM) approach which uses SmartPLS (Partial Least Square). The research results found that green products had a positive and significant effect on environmental awareness, green promotion had a positive and significant effect on environmental awareness, and brand image had a positive and significant effect on environmental awareness. Additionally, environmental awareness had a significant impact on purchase decisions.